Riset Pelaporan Keuangan Pemerintahan Selama Satu Dekade di Indonesia : Sebuah Review Literature - Deviani Deviani (Universitas Negeri Padang, 2020)
This paper aim to provides the overview of the state of research in the fields of governmental financial reporting in Indonesia over the period 2005-2015 and also explore avenue for future research. To achieve the aim, this paper reviews prior research on governmental financial reporting in Indonesia encompassing the research papers published in nine university journals, Accounting National Symposium (SNA), theses and dissertation from selected universities. A total of 28 studies were identified. Review based on the following three research question: 1) What topiks of interest to researchers, 2) what research methods are most often used, 3) what paradigm approach used by the researchers. By so doing the government's financial reporting research mapping may be obtained. The results of the analysis conducted in this paper reveals a paradigm approach undertaken in research. Moreover, the result show that, most topik of interest is disclosure area, archival and questionaire research method are still dominated. Furthermore, although there are variation related to topiks theories and research methods, a mainstream in governmental financial reporting research seems to exist. The institutional and social aspects of financial reporting are still relatively unexplored. This review suggests in order to conduct research with the diverse paradigm approaches. Each paradigm should complementary and cooperate not isolated. The literature review is limited to research papers published in Indonesian university, Indonesian postgraduates students research from overseas excluded. Finally recommended to conduct financial reporting research by discussing the institutional and social aspects. Keywords: Public Sektor Accounting; Governmental Financial Reporting; Paradigm Approach